2019
DOI: 10.1159/000497306
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <b><i>C9ORF72</i></b> Expansion in a Large Series of Patients with Idiopathic Normal-Pressure Hydrocephalus

Abstract: Background/Aims: The C9ORF72 expansion is known to cause frontotemporal lobar degeneration (FTLD) and amyotrophic lateral sclerosis (ALS). We aim to identify the prevalence of the C9ORF72 expansion in idiopathic normal pressure hydrocephalus (iNPH). Methods: We analysed the C9ORF72 expansion in a large cohort of patients with possible iNPH (n = 487) and cognitively intact elderly controls (n = 432; age > 65 years). Results: While the C9ORF72 expansion was detected in 1.6% (n = 8/487) of cases with possible iNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The systematic analysis of iNPH criteria in our bv-FTLD cohort probably allowed us to evidence this previously unknown association. Interestingly, a recent study reported a 1.6% prevalence of C9orf72 expansion (one major genetic cause of bv-FTLD) in an iNPH group, whereas no such expansion was observed in the control group, 20 suggesting a genetic link between iNPH and bv-FTLD.…”
Section: Discussionmentioning
confidence: 97%
“…The systematic analysis of iNPH criteria in our bv-FTLD cohort probably allowed us to evidence this previously unknown association. Interestingly, a recent study reported a 1.6% prevalence of C9orf72 expansion (one major genetic cause of bv-FTLD) in an iNPH group, whereas no such expansion was observed in the control group, 20 suggesting a genetic link between iNPH and bv-FTLD.…”
Section: Discussionmentioning
confidence: 97%
“…In this respect, it is notable that elderly patients with FTD and concomitant hydrocephalus can show clinical improvement following cerebrospinal fluid removal. 70 , 71 Assaying cerebrospinal fluid pressure in TDP-43 Q331K mice would therefore be of interest. Nonetheless, our observation that frank hydrocephalus occurred in a small number of juvenile TDP-43 Q331K mice is enough to suggest that a developmental contribution towards ventricular enlargement in mutants is likely.…”
Section: Discussionmentioning
confidence: 99%
“…While this ventriculomegaly could be due to loss of brain parenchyma, it could also reflect hydrocephalus. In this respect, it is notable that elderly patients with FTD and concomitant hydrocephalus can show clinical improvement following cerebrospinal fluid (CSF) removal (Korhonen et al, 2017;Korhonen et al, 2019). Assaying CSF pressure in TDP-43 Q331K mice would therefore be of interest.…”
Section: Discussionmentioning
confidence: 99%